Підвищення ефективності процесу алмазного доведення сферичної поверхні деталі з кераміки медичного призначення - Пузирьов, О.Л. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2007)
The problem of effectiveness increase of process of diamond lapping of a precision spherical surface of a ceramic detail is surveyed on an instance of the head of hip joint prosthesis. This increase happens at the expense of use of the new way of machining to twirl of a detail around of two axes intersected in center of an orb, and equation of loading of a cutting region.